PEMANFAATAN E-COMMERCE UNTUK MENDUKUNG UMKM DALAM PEMASARAN STUDY KASUS “PARAS SNACK” - Aprilia Kristanti; Donna Setiawati; Dwi Kristiani (JITU : Journal Informatic Technology And Communication, 2018)
Research titled Utilization of E-commerce To Support UMKM In Marketing Study Case "Paras Snack". UKM Paras Snack is one of Small and Medium Enterprises which engaged in sales of snacks typical of Boyolali district such as milk crackers, milk dodol, milk sticks, fennel sticks, carrot sticks, cheese sticks, dragon fruit sticks, betel leaf sticks, papaya leaf chips, celery chips, balado sticks, jerky cassava leaves, katuk leaf sticks, kelor leaf sticks.. Product marketing system at UKM Paras Snack is still very simple that is by way of oral delivery by some people who have family relation or work relation with UKM Paras Snack. As for the order process, consumers still have to go directly to the address of UKM Paras Snack. So consumers who are far outside the area do not know the available address, so reluctant to come directly. The purpose of this research is to design, implement, and test e-commerce applications based on E-commerce on UKM Paras Snack, Produce Ecommerce web for product marketing on UKM Paras Snack. The research methodology used is waterfall, object modeling using UML. For coding using PHP and for database using Mysql. The results achieved is an e-commerce web to facilitate the promotion and facilitate consumers in ordering products